2013
DOI: 10.1002/qre.1586
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Maximum Exponentially Weighted Moving Average Control Chart for Monitoring Process Mean and Variability

Abstract: Maximum exponentially weighted moving average (MaxEWMA) control charts have gained considerable attention for detecting changes in both process mean and process variability. In this paper, we propose an improved MaxEWMA control charts based on ordered ranked set sampling (ORSS) and ordered imperfect ranked set sampling (OIRSS) schemes for simultaneous detection of both increases and decreases in the process mean and/or variability, named MaxEWMA‐ORSS and MaxEWMA‐OIRSS control charts. These MaxEWMA control char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“… and Haq et al . , respectively. It is worth mentioning that the MaxEWMA‐ODRSS control chart performs uniformly better than the control charts considered here, that is, all of the out‐of‐control ARLs and SDRLs of the MaxEWMA‐ODRSS control chart are uniformly less than those with the optimal MaxEWMA‐SRS, optimal MaxGWMA‐SRS and MaxEWMA‐ORSS control charts.…”
Section: Performance Comparisons Of Control Chartsmentioning
confidence: 99%
See 2 more Smart Citations
“… and Haq et al . , respectively. It is worth mentioning that the MaxEWMA‐ODRSS control chart performs uniformly better than the control charts considered here, that is, all of the out‐of‐control ARLs and SDRLs of the MaxEWMA‐ODRSS control chart are uniformly less than those with the optimal MaxEWMA‐SRS, optimal MaxGWMA‐SRS and MaxEWMA‐ORSS control charts.…”
Section: Performance Comparisons Of Control Chartsmentioning
confidence: 99%
“…The values of ARLs and SDRLs of the MaxEWMA‐OIRSS control chart are taken from Haq et al . . It is clear that, even with imperfect rankings, the proposed MaxEWMA‐OIDRSS control chart turns out to be more sensitive than its counterparts when detecting all different shifts in the process mean and/or process dispersion.…”
Section: Performance Comparisons Of Control Chartsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, joint monitoring of process mean and dispersion in both univariate and multivariate cases has been considered by some researchers. Simultaneous monitoring of the mean and variance in univariate process has been studied by Khoo et al [22], Zhang et al [23], Guh [24], Memar and Niaki [25], Teh et al [26], Sheu et al [27], Haq et al [28], and Prajapati and Singh [29]. The simultaneous monitoring of multivariate process mean vector and covariance matrix has also been addressed by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the RSS‐based mean charts are more powerful than the Shewhart mean chart based on SRS. For more details about the control charts based on different RSS schemes, refer to Abujiya and Muttlak, Abujiya et al , Abujiya et al , Al‐Omari and Haq, Mehmood, Haq, Haq et al , Haq et al , and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%